Herbal Approaches for Malaria: A Review - Ancheria, Rahul Kumar; Singh, Jitendra; Khichi, M. P; Chaturvedi, Saurabh; Khan, Shahid (Asian Journal of Pharmaceutical Research and Development, 2018)
Malaria is caused by Plasmodium parasites. Malaria is one of the most important tropical infectious diseases. The incidence of malaria worldwide is estimated to be 300–500 million clinical cases each year with a mortality of between one and three million people worldwide annually. Malaria control efforts need to identify associated factors and to integrate these efforts with the information, education and communication campaigns and behavior change communication campaigns that are targeting the community of this region. The increasing levels of malaria parasite drug resistance, the herbal knowledge of indigenous communities for malaria treatment can play an important role in identification of any new antimalarial plants that is yet to be discovered.